Power to the molecules [nanometer-size switch]. - Geppert, L. (IEEE spectrum)
Hewlett-Packard Co., is developing a nanometer-size switch that has the power to amplify a signal. This power is one of the great features of transistors because it allows a signal to pass through a circuit without petering out. The switch consists of a single molecular layer sandwiched between two metal wires. HP achieved the gain it needed by using the so-called molecular crossbar, made from two switches. Each switch connects to its own control wire, which supplies it with voltage pulses. The two switches also connect to a common latch wire, which carries either a high or a low voltage. Together, the two switches encode a single bit.